Kinetics and Oxidation of 3,5-Dimethyl-2,6-diaryl piperidin-4-one Oximes by Pyridinium Chlorochromate - Janibai, T.S.; Santhi, S. (Asian Journal of Chemistry, 2011)
Kinetics of oxidation of 3,5-dimethyl-2,6-diaryl piperidin-4-one oximes by pyridinium chlorochromate have been studied in aqueous acetic acid medium. The oxidation is first order each in [oxidant] and [substrate]. The reactions are acid catalyzed. The effect of ionic strength on the reaction rate is negligible. The reaction rates are accelerated by increasing the dielectric strength of the medium indicating a polar mechanism. The reactions are followed at four different temperatures and the activation parameters computed. Based on the results obtained a plausible mechanism is proposed. The reactivity sequence is: For para substituted aryl compounds = H > 4-Cl > 4-Me > 4-OMe; For ortho substituted aryl compounds = H > 2-Me > 2-OMe > 2-Cl.